Primary Raynaud’s Disease in a Young Adult: A Case Report - Naufal Gusti; Maya Safira (MAHESA : Malahayati Health Student Journal, 2026)
ABSTRACT Raynaud’s phenomenon (RP) is characterized by intermittent vasospasm and subsequent ischemia of the extremities, typically triggered by cold exposure or emotional stress. This leads to a distinct triphasic discoloration of the fingers or toes, progressing from pallor to hyperemia. This case report describes a 20-year-old woman presenting with a 1-year history of episodic bilateral finger discoloration (pallor, cyanosis, erythema) triggered by cold exposure, consistent with primary Raynaud's phenomenon. Physical examination revealed no digital ulcers or skin changes, and basic laboratory tests were unremarkable, though autoimmune serology was unavailable due to resource limitations. The patient's photograph documenting an acute attack provided valuable diagnostic support. Management emphasized conservative measures including cold avoidance and behavioral modifications, which successfully controlled symptoms. This case highlights the clinical diagnosis of primary RP in resource-constrained settings, the utility of patient-documented evidence, and the effectiveness of non-pharmacological approaches. Keywords: Ischemia, Raynaud phenomenon, Vasospasm.